Risk of malignancy in follicular thyroid neoplasm - Zimny, M.; Selkinski, I.; Blasius, S.; Rink, T.; Schroth, H.-J.; Grünwald, F. (Nuklearmedizin - NuclearMedicine, 2012)
The cytological diagnosis of follicular neoplasm is a common finding in fine needle aspiration cytology (FNAC) of thyroid nodules and includes benign disease as well as differentiated thyroid cancer. The aim of the study is to determine if thyrotropin is a predictive factor for a malignant nature of follicular neoplasm. Patients, methods: The records of 119 patients with follicular neoplasm on FNAC, who underwent surgery for final diagnosis, were reviewed retrospectively. The predictive value of serum parameters including thyrotropin, thyroglobulin, and anti-thyroid antibodies, ultrasonographic criteria and clinical variables was evaluated by univariate analysis and logistic regression analysis. Results, discussion: Patients with malignant nodules showed a higher thyrotropin concentration compared to patients with benign nodules (median 1.6 mU/l, interquartile range 1.4–3.0 mU/l vs. median 1.2 mU/l, interquartile range 0.8–1.6 mU/l, p < 0.01). ROC-analysis of thyrotropin revealed an optimal cut off value to differentiate benign and malignant nodules of 1.34 mU/l. The incidence of malignancy was 30.3% for a thyrotropin concentration higher than 1.34 mU/l compared to 6.4% for a thyrotropin concentration lower than or equal to 1.34 mU/l. On univariate analysis thyroglobulin higher than 300 ng/ml, positive anti-thyroid antibodies, hypoechogenicity, and ill-defined margins, respectively, were also significantly associated with malignancy. On logistic regression analysis higher thyrotropin concentrations, ill-defined margins, and thyroglobulin higher than 300 ng/ml, respectively, were independent predictive factors for malignancy (OR 20.0, 10.7, and 22.7, respectively). Conclusion: Higher thyrotropin concentrations are predictive for a malignant nature of follicular neoplasm.
Keywords: Thyroid nodule; follicular neoplasm; follicular proliferation; thyrotropin; thyroid carcinoma